Investigations on a possible substitution of resonant wood in plates of musical instruments by synthetic materials - HOLZ, D. (Archives of Acoustics, 1979)
Since resonant plates in stringed musical instruments are made from coniferous woods, particularly from spruce, with maximum quality requirements, investigations were carried out in order to test the use of other materials for this purpose. These were aluminium plates with two types of visco-elastic layer, and laminates of glass fibre reinforced epoxy and unsaturated polyester resin, with reinforcements of several types, but preferably unidirectional fibres. The conclusions resulting from the measured data of sound velocity and damping in the audible frequency range only encourage further research upon laminates of glass fibre reinforced plastics.